2009
DOI: 10.1097/aud.0b013e31819342cf
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Tone Perception with HiResolution and HiResolution 120 Sound-Processing Strategies in Pediatric Mandarin-Speaking Cochlear Implant Users

Abstract: Objectives-Lexical tone recognition tends to be poor in cochlear implant users. The HiResolution (HiRes) sound-processing strategy is designed to better preserve temporal fine structure, or the detailed envelope information, of an acoustic signal. The newer HiRes 120 strategy builds on HiRes by increasing the amount of potential spectral information delivered to the implant user. The purpose of this study was to examine lexical tone recognition in native Mandarin Chinese-speaking children with cochlear implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 41 publications
4
83
0
Order By: Relevance
“…Therefore, transmitting more fine structure through cochlear implants to users might be an effective approach to improving pitch perception for them (e.g., Nie et al 2005). So far, however, little evidence has shown that any of the fine-structure strategies would make a dramatic improvement for lexical tone perception or music perception in cochlear implant users (e.g., Riss et al 2008Riss et al , 2009Han et al 2009;Firszt et al 2009;Schatzer et al 2010). Many studies have shown that cochlear implant users could only detect differences in pitch for frequencies up to about 300 Hz (e.g., Shannon 1983; Zeng 2002), which is much poorer than that observed in normal-hearing listeners (Carlyon and Deeks 2002).…”
Section: Implications For Cochlear Implantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, transmitting more fine structure through cochlear implants to users might be an effective approach to improving pitch perception for them (e.g., Nie et al 2005). So far, however, little evidence has shown that any of the fine-structure strategies would make a dramatic improvement for lexical tone perception or music perception in cochlear implant users (e.g., Riss et al 2008Riss et al , 2009Han et al 2009;Firszt et al 2009;Schatzer et al 2010). Many studies have shown that cochlear implant users could only detect differences in pitch for frequencies up to about 300 Hz (e.g., Shannon 1983; Zeng 2002), which is much poorer than that observed in normal-hearing listeners (Carlyon and Deeks 2002).…”
Section: Implications For Cochlear Implantsmentioning
confidence: 99%
“…Contemporary cochlear implant technology has provided unfavorable lexical tone perception for tone language speakers (e.g., Xu et al 2002Wei et al 2004;Xu and Pfingst 2008;Zhou et al 2008;Han et al 2009;Wang et al 2011; see Xu and Zhou 2011 for a review). Previous studies based on the measurement of normal-hearing listeners have demonstrated that fine structure is more critical for pitch perception than temporal envelope (e.g., Smith et al 2002;Xu and Pfingst 2003;Kong and Zeng 2006).…”
Section: Implications For Cochlear Implantsmentioning
confidence: 99%
“…Ongoing efforts to increase fine structure via the creation of "virtual" electrodes (e.g., McDermott and McKay, 1994;Geurts and Wouters, 2004;Firszt et al, 2007;Berenstein et al, 2008;Landsberger and Srinivasan, 2009) or the provision of fine temporal detail (e.g., Rubinstein et al, 1999;Arnoldner et al, 2007;Riss et al, 2009) have met with limited success. In general, results show some improvement in pitch detection or discrimination, but limited gains to speech reception in noise (Berenstein et al, 2008;Firszt et al, 2009;Han et al, 2009;Riss et al, 2009;Shannon et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Of the nine fully revised studies, three were taken off the systematic review -one for testing a version of the HiRes 120 1 strategy research version called SpecRes and two other studies were taken off because of the methodological design presented 2,3 , that is, studies which made a speech perception longitudinal assessment in CI users after conversion from the HiRes to HiRes 120 strategy; nonetheless, they did not have a control group and did not reassess the auditory performance of the participants with the HiRes strategy after using the HiRes 120. This made unfeasible the maintenance of these systematic review studies, since their results could have been influenced by the learning effect, in other words, performance improvement did not happen thanks to the strategy change, but rather by the entire auditory perception, based on a greater auditory experience with the CI.…”
Section: Resultsmentioning
confidence: 99%